Analisis Interferensi Bahasa Daerah Nias terhadap Bahasa Indonesia di Garu II Medan Amplas - Halimul Maduwu; Alfitriana Purba; Sutikno Sutikno; Abdullah Hasibuan; Abdul Mujib (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2025)
This research aims to analyze forms of phonological interference in the use of Indonesian by speakers of the Nias regional language in Garu II, Medan Amplas. The background of this research is based on the fact that the Nias people, as a bilingual group, often experience difficulties in pronouncing Indonesian according to the rules, resulting in symptoms of phonological deviations such as deletions, changes and additions of phonemes. Using qualitative descriptive methods and triangulation techniques (observation, interviews, documentation), this research found three main forms of interference: (1) deletion of the final phoneme (example: "jalan" becomes "jala"), (2) changes in phonemes (example: "kaya" becomes “kayo”), and (3) the addition of phonemes (example: “although” becomes “walampun”). Factors causing interference include the social environment, first language habits, low vocabulary mastery, and weak loyalty to the second language. It is hoped that the results of this research can enrich the study of phonology and become a reference in developing Indonesian for bilingual communities.